Reinforcing of Biologically Derived Apatite with Commercial Inert Glass - OKTAR, FAİK NÜZHET; EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN (SAGE PUBLICATIONS LTD, 2009)
Apatite-based ceramics, derived from fine powder of calcinated bovine-bone (BHA), were successfully reinforced with 5 and 10 wt% commercial inert glass (CIG), which contained biocompatible elements, via sintering at different temperatures between 1000 and 1300 degrees C. The products were subjected to mechanical testing and microstructural and crystallographic analyses. Comparison of the experimental results with those from earlier similar studies shows that CIG is superior for reinforcing of BHA ceramics compared with other bioactive glasses. Provided that the CIG addition does not exceed a certain limit, optimally being approximately 5 wt%, the resultant BHA-CIG materials can exhibit high strength after sintering and remarkable resistance toward over-firing at 1300 degrees C. The influence of the amount of CIG on the developed microstructure and crystalline structure after sintering at different temperatures is discussed.
Keywords: apatite; inert glass; cullet; sintering; mechanical properties; microstructure; BOVINE HYDROXYAPATITE BHA; ALUMINA COMPOSITE COATINGS; MECHANICAL-PROPERTIES; BONE; ENAMEL